The energy saving guide tables for assessing the profitability of energy saving measures with explanatory notes and worked examples - Helcke, George (Pergamon Press, 1981)
The Energy Saving Guide: Tables for Assessing the Profitability of Energy Saving Measures with Explanatory Notes and Worked Examples describes the means of comparing investment in energy saving measures with other types of financial investment. This book is composed of nine chapters and begins with an introduction to the Present Value concept and the effect of energy price inflation rate on energy savings. The next chapters consider the annual maintenance charges of an energy saving system and the investment deferment to achieve cost effectiveness within a defined period. A chapter presents several examples to illustrate the method of assessing the cost-effectiveness of various energy saving investments. The final chapters provide the mathematical background and tables for the Present Value concept and values. This book is intended for economists and non-specialists.--Provided by publisher.